If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 6r + -5 = 8r + 21 + -6r Reorder the terms: 6 + -5 + 6r = 8r + 21 + -6r Combine like terms: 6 + -5 = 1 1 + 6r = 8r + 21 + -6r Reorder the terms: 1 + 6r = 21 + 8r + -6r Combine like terms: 8r + -6r = 2r 1 + 6r = 21 + 2r Solving 1 + 6r = 21 + 2r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-2r' to each side of the equation. 1 + 6r + -2r = 21 + 2r + -2r Combine like terms: 6r + -2r = 4r 1 + 4r = 21 + 2r + -2r Combine like terms: 2r + -2r = 0 1 + 4r = 21 + 0 1 + 4r = 21 Add '-1' to each side of the equation. 1 + -1 + 4r = 21 + -1 Combine like terms: 1 + -1 = 0 0 + 4r = 21 + -1 4r = 21 + -1 Combine like terms: 21 + -1 = 20 4r = 20 Divide each side by '4'. r = 5 Simplifying r = 5
| X-(1-x)=2 | | -2x^2+20x-47=0 | | 5(6-7)=10 | | X+3x+2=5x+6 | | -2x^2+20x-36=0 | | -2x^2+20x-39=0 | | 2(x+5)-x=x+10 | | 4x-3=2x-1/3 | | 45=9x+9 | | (Y)+y=2 | | -10x-17=167 | | 3*x+20=5*x-4 | | 4a^5-500a^2=0 | | 68hm=km | | r^2+12r-189=0 | | 9w+1+3(w+2)= | | 8x-14=x^2+x-2 | | 3-(4x-3)=1 | | -45+m=24 | | 6n-24=9-3n-3 | | K^2+8=56 | | p(2+5p)= | | 3/2=x/11 | | 2x-35(4+5)=40 | | 2lnx-1= | | (4x-52)+(x+32)+(.5x+46)= | | x-5=5+x | | 2z+12=3-z | | 3x+5+2x-1=3x+17 | | 6a-8=3a+7 | | 7x-2x+7=2x+32 | | 8+2(8x-6)=2(4+7) |